A comparative analysis of profit inefficiency and productivity convergence between Taiwanese and Chinese banks. Issue 3 (July 2020) - Chen, Xiang; Fu, Tsu-Tan; Juo, Jia-Ching; Yu, Ming-Miin
To insure a proper and meaningful productivity assessment of DMUs with different production technologies, this article develops a difference-based profit metafrontier Luenberger productivity indicator. Adopting the proposed model, we empirically measure the profit inefficiency and examine the profit productivity convergence for samples banks consisting of 31 Taiwanese banks and 50 Chinese city banks over 2010–2014. Empirical results show that Chinese banks perform better in profit efficiency than Taiwanese banks. While Chinese banks have better technology in profit creation than Taiwanese banks, the latter may reap much higher profit gain than the former if they can adopt the profit metafrontier. The results of the profit metafrontier Luenberger productivity indicator analysis show that both Chinese and Taiwanese banks have experienced declines in profit productivity. However, the results also indicate a divergence in productivity growth for Chinese city banks and a convergent productivity growth for Taiwanese banks. JEL CLASSIFICATION: D20, G21, P34